2008
DOI: 10.1111/j.1365-2672.2007.03696.x
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of lactic acid producing bacteria from the rumen of dairy cattle grazing on improved pasture supplemented with wheat and barley grain

Abstract: Aims:  To identify and characterize the major lactic acid bacteria in the rumen of dairy cattle grazing improved pasture of rye grass and white clover and receiving a maize silage and grain supplement with and without virginiamycin. Methods and Results:  Eighty‐five bacterial isolates were obtained from the rumen of 16 Holstein‐Friesian dairy cows. The isolates were initially grouped on the basis of their Gram morphology and by restriction fragment length polymorphism analysis of the PCR amplified 16S rDNA. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In the Mie fecal samples, L. animalis, L. johnsonii, L. reuteri, and L. plantarum were found in all the dairy cows tested; thus, except for L. plantarum, the LAB species usually detectable in the gut were indeed seen in the present study (Krause et al, 2003;Hernandez et al, 2008;Nader-Macías et al, 2008). Lactobacillus acetotolerans, L. suebicus, and L. casei appeared to survive in the Mie dairy cow feces.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In the Mie fecal samples, L. animalis, L. johnsonii, L. reuteri, and L. plantarum were found in all the dairy cows tested; thus, except for L. plantarum, the LAB species usually detectable in the gut were indeed seen in the present study (Krause et al, 2003;Hernandez et al, 2008;Nader-Macías et al, 2008). Lactobacillus acetotolerans, L. suebicus, and L. casei appeared to survive in the Mie dairy cow feces.…”
Section: Discussionmentioning
confidence: 51%
“…However, as Rodriguez-Palacios et al (2009) acknowledged, the isolation of L. plantarum from the bovine gut is rare. The LAB species usually detected in the gut are Streptococcus bovis, Lactobacillus vitulinus, Lactobacillus ruminis, Lactobacillus johnsonii, and Lactoabacillus murinus (Krause et al, 2003;Hernandez et al, 2008;Nader-Macías et al, 2008). This raises a debate on how to select LAB species for developing probiotic supplements.…”
Section: Introductionmentioning
confidence: 98%
“…There have been additional studies of the bacterial composition of the gut in other animals, including chickens (Dumonceaux et al, 2006), mice (Yap et al, 2008), pigs (Hill et al,8 2005), and cows (Hernandez et al, 2008). These studies have revealed that each animal species has a gut microbiota that is unique and representative of that species.…”
Section: Identification Of Microorganisms In the Gutmentioning
confidence: 99%
“…Isolates of O. uli and O. profusa are regularly recovered from disease sites in the human mouth (Munson et al, 2002(Munson et al, , 2004Hooper et al, 2006) and sometimes from blood of humans with local oral or gastrointestinal infections (Lau et al, 2004;Bahrani-Mougeot et al, 2008). Olsenellae are found in the healthy (Ozutsumi et al, 2005;Cho et al, 2006;Hernandez et al, 2008) and acidotic (Tajima et al, 2000) bovine rumen. Moleculargenetic studies have also reported the detection of Olsenella-related clones in the gastrointestinal tracts of humans (Martinez-Medina et al, 2006;Khachatryan et al, 2008;Krogius-Kurikka et al, 2009), pigs (Leser et al, 2002;Tsukahara & Ushida, 2002;Dowd et al, 2008), wallabies (Chhour et al, 2008) and chickens (Lu et al, 2003) and in diverse anaerobic environmental sites (Bowman et al, 2006;Wongtanet et al, 2007;Weiss et al, 2008;Rivière et al, 2009).…”
mentioning
confidence: 99%